2020
DOI: 10.3390/pathogens9070591
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infection of Skunk Adenovirus-1, Listeria monocytogenes, and a Regionally Specific Clade of Canine Distemper Virus in One Gray Fox (Urocyon cinereoargenteus) and Concurrent Listeriosis and Canine Distemper in a Second Gray Fox

Abstract: One free-ranging Gray fox (Urocyon cinereoargenteus) underwent autopsy following neurologic disease, with findings including morbilliviral inclusions and associated lesions in numerous tissues, adenoviral intranuclear inclusions in bronchial epithelial cells, and septic pleuropneumonia, hepatitis, splenitis, and meningoencephalitis. Molecular diagnostics on fresh lung identified a strain within a distinct clade of canine distemper that is currently unique to wildlife in New England, as well as the emerging mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The lower CDV seropositivity in gray foxes is consistent with a study of CDV Ab prevalence in foxes from Wisconsin that reported CDV Ab prevalence values of 11% and 0% for red ( N = 57) and gray ( N = 32) foxes, respectively ( 17 ). Gray foxes have been demonstrated to be susceptible to infection with high lethality ( 18 ). Hence, the lower number of CDV-positive gray foxes may be due to fewer animals surviving infection.…”
Section: Observationmentioning
confidence: 99%
“…The lower CDV seropositivity in gray foxes is consistent with a study of CDV Ab prevalence in foxes from Wisconsin that reported CDV Ab prevalence values of 11% and 0% for red ( N = 57) and gray ( N = 32) foxes, respectively ( 17 ). Gray foxes have been demonstrated to be susceptible to infection with high lethality ( 18 ). Hence, the lower number of CDV-positive gray foxes may be due to fewer animals surviving infection.…”
Section: Observationmentioning
confidence: 99%
“…L. monocytogenes exhibits innate resistance to nalidixic acid, oxacillin, and certain third–generation cephalosporins but is not commonly resistant to antibiotics employed for treatment [ 9 , 10 , 11 ]. However, there are several reports of resistance to clinically-relevant antibiotics in L. monocytogenes and other Listeria species [ 10 , 12 , 13 , 14 ]. Thus, antimicrobial resistance (AMR) in this serious human and animal pathogen is of concern, in agreement with the global trend of growing AMR challenges in agriculture and the food chain [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the virus was also detected in pet pygmy hedgehogs with bronchopneumonia in the USA (Needle et al, 2019). Most recently, SkAdV-1 has also been reported from North American porcupines (Erethizon dorsatum) with respiratory diseases (Balik et al, 2020) and from grey fox (Urocyon cinereoargenteus) (Needle et al, 2020 A few years before the isolation of SkAdV-1 in Canada, a yet unknown AdV had been isolated from the internal organs of a dead pygmy marmoset (Callithrix pygmaea) originating from a Hungarian zoo; prior to its death the marmoset showed severe respiratory signs (G al et al, 2013). A PCRamplified fragment from the DNA polymerase gene has been sequenced.…”
mentioning
confidence: 97%
“…The homologues of ORF A can be found only in chiropteran, canine and equine-1 AdVs. The SkAdV also seems to be widely distributed, since it was reported from three continents (Asia, Europe and North America) from captive (zoo and pets) and wild animals (G al et al, 2013;Kozak et al, 2015;Madarame et al, 2016;Balik et al, 2020;Needle et al, 2020). SkAdV-1 was detected from dead or diseased animals, usually displaying respiratory disease signs (G al et al, 2013;Madarame et al, 2016;Needle et al, 2019;Ochiai et al, 2020).…”
mentioning
confidence: 99%